CD4+-mediated colitis in mice is independent of the GPR183 and GPR18 pathways - Dicker, Martina; Li, Yingcong; Giles, Daniel A.; Verstichel, Greet; Castelan, Viankail Cedillo; Ascui-Gac, Gabriel; Chou, Ting-Fang; Perez-Jeldres, Tamara; Cheroutre, Hilde; Kronenberg, Mitchell (Frontiers in Immunology, 2022)
Colitis is characterized by an exacerbated intestinal immune response, but the genetic and other mechanisms regulating immune activation remain incompletely understood. In order to identify new pathways leading to colitis, we sought to identify genes with increased expression in the colons of patients that also are near loci identified by genome wide association studies (GWAS) associated with IBD risk. One such SNP, rs9557195 was of particular interest because it is within an intron of G-protein-coupled receptor (GPR) 183, known to be important for lymphocyte migration. Furthermore, this SNP is in close proximity to the gene encoding another G-protein coupled receptor, GPR18. Analyzing publicly available datasets, we found transcripts of GPR183 and GPR18 to be increased in colon biopsies from ulcerative colitis and Crohn’s disease patients, and GPR183 was even more increased in patients resistant to TNF treatment. Expression of both genes also was increased in mouse models of colitis. Therefore, our aim was to understand if increased expression of these GPRs in the intestine is related to disease severity in colitis models. Here we investigated the role of these receptors in the T cell transfer model and the dextran sulfate sodium model. In the T cell transfer model, GPR183 expression on donor T cells, as well as on other cell types in the Rag-/- recipients, was not essential for severe colitis induction. Furthermore, deficiency in Rag-/- mice for the enzyme that synthesizes a cholesterol metabolite that is a major ligand for GPR183 also did not affect disease. Similarly, lack of GPR18 expression in T cells or other cell types did not affect colitis pathogenesis in the T cell transfer or in the dextran sulfate sodium model. Therefore, despite increased expression of transcripts for these genes in the intestine during inflammation in humans and mice, they are not required for disease severity in mouse models of colitis induced by chemical injury or T cell cytokines, perhaps due to redundancy in mechanisms important for homing and survival of lymphocytes to the inflamed intestine.